1985
DOI: 10.1136/jnnp.48.10.1025
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic neuropathy in acute intermittent porphyria.

Abstract: SUMMARY Autonomic function was assessed in subjects with acute intermittent porphyria and age-and sex-matched controls using five different bedside tests of cardiovascular reflexes. During the acute attack both parasympathetic and sympathetic tests were impaired, but subsequently improved during remission. Early parasympathetic dysfunction was also detected during remission and in latent asymptomatic acute intermittent porphyria.Acute intermittent porphyria is an autosomal dominant inborn error of metabolism c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
3

Year Published

1987
1987
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 31 publications
1
34
0
3
Order By: Relevance
“…Autonomic testing demonstrates both parasympathetic and sympathetic dysfunction during an acute attack that improves with resolution of the episode. 26 This correlates with autopsy studies, which have demonstrated demyelination and axonal degeneration of the vagus nerve and decreased density and chromatolysis of sympathetic ganglia cells. 27 …”
Section: Autonomic Neuropathysupporting
confidence: 51%
“…Autonomic testing demonstrates both parasympathetic and sympathetic dysfunction during an acute attack that improves with resolution of the episode. 26 This correlates with autopsy studies, which have demonstrated demyelination and axonal degeneration of the vagus nerve and decreased density and chromatolysis of sympathetic ganglia cells. 27 …”
Section: Autonomic Neuropathysupporting
confidence: 51%
“…B. in autonomen Ganglien,spinalen Vorderhornzellen,peripheren Neuronen, Kernen des Stammhirns, im Kleinhirn, in Schwann-Zellen und Myelinscheiden nachgewiesen werden können [1,3,5,26,30],wird in einer direkten Schädigung von Nervenzellen gesehen. Der histopathologische Befund zeigt meist eine Störung des Aufbaus der Myelinscheide sowie eine Vakuolisierung und einen Abbau der Axone in autonomen und peripheren Nerven [25].…”
Section: Desflurane In Acute Intermittent Porphyriaunclassified
“…Central nervous system involvement may present as seizure activity, depression or as an acute organic brain syndrome (confusion, delusions and hallucinations). [4][5][6][7] …”
Section: Pathogenesis Of Porphyriamentioning
confidence: 99%